Oral dabigatran etexilate versus enoxaparin for venous thromboembolism prevention after total hip arthroplasty: pooled analysis of two phase 3 randomized trials. Issue 1 (December 2015) - Eriksson, Bengt; Dahl, Ola; Rosencher, Nadia; Clemens, Andreas; Hantel, Stefan; Feuring, Martin; Kreuzer, Jörg; Huo, Michael; Friedman, Richard
Abstract Background Two phase 3 trials compared 28–35 days of treatment with oral dabigatran 220 mg or 150 mg (RE-NOVATE) or 220 mg (RE-NOVATE II) once daily with subcutaneous enoxaparin 40 mg once daily for prevention of venous thromboembolism (VTE) after elective total hip arthroplasty. Methods This prespecified pooled analysis compared the outcomes for the dabigatran 220 mg dose with enoxaparin, which included 4, 374 patients. Total VTE (venographic and symptomatic) plus all-cause mortality (primary efficacy), major VTE (proximal deep vein thrombosis [DVT] or non-fatal pulmonary embolism) plus VTE-related death, and bleeding events were evaluated. Efficacy analysis was based on the modified intention-to-treat (ITT) population and safety analysis was based on all treated patients. The common risk difference (RD) for dabigatran versus enoxaparin was estimated using a fixed effects model. Results Total VTE and all-cause mortality occurred in 6.8 % (114/1, 672) and 7.7 % (129/1, 682) (RD:–0.8 %, 95 % confidence interval [CI] –2.6 to 0.9) for dabigatran and enoxaparin, respectively. Major VTE plus VTE-related mortality occurred in 2.7 % (46/1, 714) and 4.0 % (69/1, 711) (RD: –1.4 %, 95 % CI –2.6 to –0.2) of patients receiving dabigatran 220 mg and enoxaparin, respectively. Major bleeding occurred in 1.7 % (37/2, 156) and 1.3 % (27/2, 157) (RD: 0.5 %, 95 % CI –0.2 to 1.2), for dabigatran and enoxaparin respectively. Conclusions Extended prophylaxis with oral dabigatran 220 mg once daily was as effective as enoxaparin 40 mg once daily in reducing the risk of total VTE and all-cause mortality after total hip arthroplasty, with a similar bleeding profile. The clinically relevant outcome of major VTE and VTE-related death was significantly reduced with dabigatran versus enoxaparin. Trial registration NCT00657150 andNCT00168818